Comparison of Surgical Outcomes for Arthrodesis and Arthroplasty for Thumb Carpometacarpal Osteoarthritis in Female Workers - Komura, Shingo; Hirakawa, Akihiro; Hirose, Hitoshi; Akiyama, Haruhiko (Journal of Hand and Microsurgery, 2023)
Background Both arthrodesis and trapeziectomy with ligament reconstruction and tendon interposition (T + LRTI) arthroplasty are reliable surgical procedures for thumb carpometacarpal (CMC) osteoarthritis. Here, we compared surgical outcomes between arthrodesis and T + LRTI for female workers aged over 40 years with thumb CMC osteoarthritis to determine an optimal procedure.Patients and Methods Fourteen thumbs of 13 patients who underwent arthrodesis with locking plates and 11 thumbs of 10 patients who underwent T + LRTI and were followed up for at least 12 months were retrospectively analyzed. For the two groups, we investigated the range of motion (ROM) of the thumb, grip strength, pinch strength, disabilities of the arm, shoulder, and hand (DASH) score, Hand20 score, and visual analog scale (VAS) scores for pain at 1-year follow-up and compared them between the two groups. In addition, we investigated surgical complications and resumption of work.Results Both procedures provided similar subjective outcomes in terms of Hand20 and VAS scores; however, arthrodesis provided significantly larger ROM of the metacarpophalangeal and interphalangeal joints of the thumb, grip and pinch strength, and DASH score, whereas T + LRTI provided a significantly better palmar abduction at 1-year follow-up. There were three and four postoperative complications in the arthrodesis and T + LRTI groups, respectively. One patient in the arthrodesis group had resigned, whereas two patients in T + LRTI had changed their jobs to less physically demanding ones postoperatively.Conclusion Both procedures satisfy female workers aged over 40 years with thumb CMC osteoarthritis. Nevertheless, arthrodesis can provide favorable outcomes that are equal to or better than T + LRTI.
Keywords: thumb carpometacarpal osteoarthritis; osteoarthritis; arthrodesis; arthroplasty; female workers